MP11: Emergency physician attitudes on opioid use disorder and barriers to providing buprenorphine/naloxone. (May 2020) - Webster, D.; Meyer, T.; Crain, C.; Fraser, J.; Atkinson, P.
Abstract : Introduction: Buprenorphine/naloxone (buprenorphine) has proven to be a life-saving intervention amidst the ongoing opioid epidemic in Canada. Research has shown benefits to initiating buprenorphine from the emergency department (ED) including improved treatment retention, systemic health care savings and fewer drug-related visits to the ED. Despite this, there has been little to no uptake of this evidence-based practice in our department. This qualitative study aimed to determine the local barriers and potential solutions to initiating buprenorphine in the ED and gain an understanding of physician attitudes and behaviours regarding harm reduction care and opioid use disorder management. Methods: ED physicians at a midsize Atlantic hospital were recruited by convenience sampling to participate in semi-structured privately conducted interviews. Audio recordings were transcribed verbatim and de-identified transcripts were uploaded to NVivo 12 plus for concept driven and inductive coding and a hierarchy of open, axial and selective coding was employed. Transcripts were independently reviewed by a local qualitative research expert and themes were compared for similarity to limit bias. Interview saturation was reached after 7 interviews. Results: Emergent themes included a narrow scope of harm reduction care that primarily focused on abstinence-based therapies and a multitude of biases including feelings of deception, fear of diversion, feeling buprenorphine induction was too time consuming for the ED and differentiating patients with opioid use disorder from 'medically ill' patients. Several barriers and proposed solutions to initiating buprenorphine from the ED were elicited including lack of training and need for formal education, poor familiarity with buprenorphine, the need for an algorithm and community bridge program and formal supports such as an addictions consult team for the ED. Conclusion: This study elicited several opportunities for improved care for patients with addictions presenting to our ED. Future education will focus on harm reduction care, specifically strategies for managing patients desiring to continue to use substances. Education will focus on addressing the multitude of biases elicited and dispelling common myths. A locally informed buprenorphine pathway will be developed. In future, this study may be used to advocate for improved formal supports for our department including an addictions consult team.